2022
DOI: 10.13045/jar.2021.00269
|View full text |Cite
|
Sign up to set email alerts
|

Facial Chuna Manual Therapy and Acupuncture Treatment for the Sequelae of Peripheral Facial Nerve Palsy: Two Clinical Cases

Abstract: Two patients with sequelae of peripheral facial nerve palsy were treated with Facial Chuna Manual Therapy (FCMT) and acupuncture over 6 months. The House-Brackmann (HB) scale, facial nerve grading system 2.0 (FNGS), the scale of Peitersen, the scale of Murata, and the Numeric Rating Scale (NRS) were used to assess the effects of treatment. The HB scale, FNGS and NRS scores showed improvement for both patients (Case 1: HB scale 5 to 3, FNGS 4 to 2, NRS 10 to 5; Case 2: HB scale 5 to 3, FNGS 4 to 3, NRS 10 to 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Few studies have been conducted regarding these treatment methods which increase the activity of the corresponding muscles and acupoints by direct contact with the affected side causing facial paralysis. There has been a case report 20 days after the onset of Bell's palsy [7], and another report presenting 2 cases treated for sequelae of facial palsy [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been conducted regarding these treatment methods which increase the activity of the corresponding muscles and acupoints by direct contact with the affected side causing facial paralysis. There has been a case report 20 days after the onset of Bell's palsy [7], and another report presenting 2 cases treated for sequelae of facial palsy [8].…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated the effective application of cervical spine therapy in inpatients and outpatients [6]. Additionally, 2 case reports have been published which discuss the improvement achieved by direct manipulation of the facial muscles [7,8]. However, there is no report regarding facial chuna manual therapy performed for patients who have undergone a combination of inpatient and outpatient treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a previous study [15] used Chuna not only on the cervical area but also on the face. A previous study [6] also showed that K-FCMT was effective in patients with sequelae, although patients received conventional KM treatment such as A-Tx, EA, pharmacopuncture, and herbal medicine in their acute phase. Moreover, a study [16] reported that SJS non-resistance technique-facial palsy manual therapy based on the restoration of muscle nerves by re-education of the paralyzed muscles was effective in cases that were not responsive to conventional KM treatment such as acupuncture and EA.…”
Section: Jarmentioning
confidence: 93%
“…Korean Facial Chuna Manual Treatment (K-FCMT) is a manual therapy used for patients with Bell's palsy, and it is based on various manual techniques applied to facial paralysis [5]. A previous study using K-FCMT 2-3 times a week in patients who did not improve well in the acute phase, although they received conventional KM and WM treatments, showed improvement in the sequelae of Bell's palsy [6]. However, no studies have applied K-FC-MT in patients with acute Bell's palsy.…”
Section: Introductionmentioning
confidence: 99%